AN EVALUATION OF THE EFFECTIVENESS OF THE AUTHENTIC TASK ON STUDENTS’ LEARNING ACHIEVEMENT OF PLANT ANATOMY CONCEPTS IN SURABAYA STATE UNIVERSITY - Susiyawati, Enny; Ibrahim, Muslimin; Atweh, Bill; Rahayu, Yuni Sri (JPPS (Jurnal Penelitian Pendidikan Sains), 2012)
To promote the knowledge of plant anatomy which is frequently taught using traditional method, students need to be involved in authentic learning by providing them an authentic task. Therefore, the aims of this current research are to implement a certain authentic task of plant anatomy; to evaluate the effectiveness of the task on the students? learning achievement includes their performances, knowledge mastery, and perceptions of the task; and to describe some difficulties that occurred during the implementation of the authentic task. This case study research involved a single class consisted of 25 bachelor degree students as the subjects of this research. Observation, interview, and test were implemented to collect variety information during implementation ofthe authentic task. The findings showed that the students? performance scores and the percentage of mastered indicators met the minimum mastery criteria, but the percentage of classical mastery was less than the criteria. It means the authentic task had positive impact only on students? performance, but it could not help the whole students to master the topic. However, regarding to perception, both higher and lower achiever students thought the task was authentic. Nevertheless, there were four obstacles occurred during implementation of the authentic task, they were students? confusion of the task, students? difficulty to make microscope slides,students? difficulty to identify plant structures, and the limited time. Overall, it can be concluded that, contrary to what was expected, the implemented authentic task in this study was not effective for the learners in order to get a good holistic learning achievement due to the difficulties. Therefore, in designing a well authentic task, the educators or developer need to think not only the task, but also students? skills and time allocation. Dalam rangka meningkatkan pengetahuan tentang anatomi tumbuhan yang biasanya diajarkan melalui metode tradisional, siswa perlu dilibatkan dalam pembelajaran autentik melalui pemberian tugas autentik. Oleh karenanya, tujuan penelitian ini ialah untuk menerapkan suatu tugas autentik tentang anatomi tumbuhan; untuk mengevaluasi keefektivan tugas tersebut terhadap hasil belajar siswa yang meliputi hasil kinerja, ketuntasan materi ajar, dan persepsi siswa terhadap tugas tersebut; serta untuk mendeskripsikan kesulitan-kesulitan yang terjadi selama penerapan tugas autentik. Penelitian dengan tipe penyelidikan kasus ini melibatkan satu kelas yang terdiri atas 25 siswa S1 sebagai subjek penelitian. Pengamatan, wawancara, dan tes diterapkan untuk mengumpulkan berbagai informasi selama penerapan tugas autentik. Hasil penelitian menunjukkan bahwa skor kinerja siswa dan persentase ketuntasan indikator memenuhi kriteria ketuntasan minimum, tetapi persentase ketuntasan klasikal tidak mencapai kriteria tersebut. Hal tersebut berarti tugas autentik yang diterapkan memiliki dampak positif hanya terhadap hasil kinerja siswa, tetapi tugas tersebut belum dapat membantu seluruh siswa untuk menuntaskan materi ajar. Walaupun demikian, berkaitan dengan persepsi siswa, baik siswa yang memperoleh nilai tinggi maupun rendah menganggap tugas tersebut autentik. Akan tetapi, terdapat empat kendala yang terjadi selama penerapan tugas autentik tersebut, yaitu: kebingungan siswa terhadap tugas yang diberikan; kesulitan siswa dalam membuat preparat dan mengidentifikasi struktur tanaman; serta keterbatasan waktu yang tersedia. Jadi, dapat disimpulkan bahwa, berbeda dengan yang diharapkan, tugas autentik yang diterapkan dalam penelitian ini tidak effektif bagi siswa dalam rangka memperoleh hasil belajar holistik yang baik karena kesulitan-kesulitan yang muncul selama penerapannnya. Oleh karena itu, dalam merancang suatu tugas autentik yang baik, pengajar perlu memikirkan tidak hanya tugas autentik itu sendiri, tetapi juga keterampilan siswa dan alokasi waktu.